2001
DOI: 10.1177/014920630102700503
|View full text |Cite
|
Sign up to set email alerts
|

Gender and discipline in the workplace: Wait until your father gets home

Abstract: This study examined recipients' perceptions of workplace discipline. Females delivering discipline were perceived to be less effective and less fair than males. Both recipients' biases and behavior differences by male and female supervisors appear to contribute to reduced effectiveness. These results suggest the need to raise the awareness of managers and subordinates regarding potential negative reactions to females administering discipline. Special training in discipline delivery for female managers may also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 45 publications
(58 reference statements)
3
9
0
Order By: Relevance
“…These findings support many studies (see Powell, 1988) and refute some new findings (Vroom, 2000) that female managers' efforts to discipline worker were found to be less effective and face more negative emotional response, than their male counterparts efforts (Atwater et al, 2001). …”
Section: Fem Inine Aspects O F Educational Managementsupporting
confidence: 83%
“…These findings support many studies (see Powell, 1988) and refute some new findings (Vroom, 2000) that female managers' efforts to discipline worker were found to be less effective and face more negative emotional response, than their male counterparts efforts (Atwater et al, 2001). …”
Section: Fem Inine Aspects O F Educational Managementsupporting
confidence: 83%
“…For example, a recent study by Brescoll and Uhlmann (2008) showed that both male and female participants assigned less status and lower salaries to women who expressed anger compared to their angry male counterparts. Similar findings have been documented in reaction to observations of other types of agentic behaviors, such as self-promotion (Rudman, 1998), competitiveness (Rudman & Glick, 1999), task-oriented speaking styles (Carli, LaFleur, & Loeber, 1995), authoritative leadership style (Eagly, Makhijani, & Klonsky, 1992), administering discipline (Atwater, Carey, & Waldman, 2001;Brett, Atwater, & Waldman, 2005) or criticism (Sinclair & Kunda, 2000), and initiation of salary negotiations (Bowles, Babcock, & Lai, 2007). Negative reactions to prescriptive violations, however, are not necessarily dependent on the behavior of the actor but can also be simply inferred from the context.…”
Section: Power-relevant Stereotypessupporting
confidence: 65%
“…Teachers are often less imbued with expectations about girls' limitations since girls are academically outperforming boys consistently until later in life. Consistent with Dweck's (1999) explanation, Alwater, Carey, and Waldman (2000) suggest that the feedback girls receive in school is the reason for women being less confident about their abilities than men. Feedback given to boys in school is often directed toward non-intellectual qualities such as misconduct, while feedback for girls is more often specifically relevant to ability.…”
Section: Varying Levels Of Goal Orientationsupporting
confidence: 70%